Josie Mpama/Palmer : get up and get moving - Edgar, Robert R. (Ohio short histories of Africa., 2020)
"While African National Congress narratives dominate much of the scholarship on South Africa's freedom struggle, Josie Mpama/Palmer's political life offers a different perspective. Highly critical of the patriarchal attitudes that hindered black women from actively participating in politics, Mpama/Palmer was an outspoken advocate for women's social equality and encouraged black women to become more involved in national conversations. The first black woman to join the Communist Party of South Africa and an antiapartheid activist, Josie Mpama/Palmer remained involved in critical issues all her life, especially protests against Bantu Education and other forms of racial and sexist discrimination. She was an integral figure in establishing the Federation of South African Women, an organization open to women of all races. Mpama/Palmer's activism and political legacy would become an inspiring example for women in South Africa and around the world to get up and get moving"--